2016
DOI: 10.4049/jimmunol.1501707
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Igα-Deficient Mature B Cells Requires BAFF-R Function

Abstract: Expression of a functional BCR is essential for the development of mature B cells and has been invoked in the control of their maintenance. To test this maintenance function in a new experimental setting, we used the tamoxifen-inducible mb1-CreER(T2) mouse strain to delete or truncate either the mb-1 gene encoding the BCR signaling subunit Igα or the VDJ segment of the IgH (H chain [HC]). In this system, Cre-mediated deletion of the mb-1 gene is accompanied by expression of a GFP reporter. We found that, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 97 publications
(125 reference statements)
1
18
0
Order By: Relevance
“…Taken together, these results might indicate a role for B cells in CFS pathophysiology, as is supported from studies of cellular immunology: Brenu and co-workers reported a decrease in immature B cells and an increase in memory B cells among CFS patients [74], whereas Bradley and co-workers [75] and Mensah and co-workers [76] found subtle distortions in the proportion of B cell subsets. Alterations of immunoglobulin levels in CFS have also been reported [77], but was not identified in the present material, which is not surprising given the strong propensity of compensatory mechanisms to ensure normal immunoglobulin levels in circulation despite changes in B cell function [78]. …”
Section: Discussionmentioning
confidence: 44%
“…Taken together, these results might indicate a role for B cells in CFS pathophysiology, as is supported from studies of cellular immunology: Brenu and co-workers reported a decrease in immature B cells and an increase in memory B cells among CFS patients [74], whereas Bradley and co-workers [75] and Mensah and co-workers [76] found subtle distortions in the proportion of B cell subsets. Alterations of immunoglobulin levels in CFS have also been reported [77], but was not identified in the present material, which is not surprising given the strong propensity of compensatory mechanisms to ensure normal immunoglobulin levels in circulation despite changes in B cell function [78]. …”
Section: Discussionmentioning
confidence: 44%
“…An alternative interpretation of these data is that the Igβ/CD19 module is also expressed on normal B cells and that it becomes detectable after BCR internalization. Continuous signaling from the Igβ/CD19 receptor module may also be the explanation for the long‐term survival of mature murine B cells that upon inducible Cre‐mediated deletion of the Igα gene, become BCR‐negative (Levit‐Zerdoun et al , 2016). Indeed, similar to what we have observed with Igβ‐only Ramos B cells, Igα‐deficient murine B cells can flux calcium upon exposure to anti‐Igβ antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…We crossed the floxed B1‐8f/Δ Ig transgenic mice (Lam et al , 1997) with mb1‐CreERT2 mice (Hug et al , 2014) to generate the B1‐8f/Δ mb1CreERT2 mice (Hobeika et al , 2015; Levit‐Zerdoun et al , 2016). The mice were induced as reported previously to generate BCR − B cells (Becker et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice express a B cell-specific Cre recombinase from the Ig-encoding mb-1 locus, which, upon tamoxifen treatment, induces the deletion of the B1-8 fl allele, resulting in the generation of HC-deficient B cells. The HC-deficient B cells were obtained at day 7 after tamoxifen treatment when an abundant number of these cells were still present in mb1-CreER T2 ; B1-8 fl mice before they were lost at later time points (44)(45)(46). These cells (denoted as HC −/− cells), identified by gating on IgM-and IgD-negative populations ( fig.…”
Section: Bambl Induces Ca 2+ Release That Is Dependent On Bcr Expressmentioning
confidence: 99%